Integrative analysis of chromatin states in Arabidopsis identified potential regulatory mechanisms for natural antisense transcript production. (26th October 2012) - Luo, Chongyuan; Sidote, David J.; Zhang, Yi; Kerstetter, Randall A.; Michael, Todd P.; Lam, Eric
Summary Genome‐wide analyses of epigenomic and transcriptomic profiles provide extensive resources for discovering epigenetic regulatory mechanisms. However, the construction of functionally relevant hypotheses from correlative patterns and the rigorous testing of these hypotheses may be challenging. We combined bioinformatics‐driven hypothesis building with mutant analyses to identify potential epigenetic mechanisms using the model plant Arabidopsis thaliana. Genome‐wide maps of nine histone modifications produced by ChIP‐seq were used together with a strand‐specific RNA‐seq dataset to profile the epigenome and transcriptome of Arabidopsis. Combinatorial chromatin patterns were described by 42 major chromatin states with selected states validated using the re‐ChIP assay. The functional relevance of chromatin modifications was analyzed using the ANchored CORrelative Pattern (ANCORP) method and a newly developed state‐specific effects analysis (SSEA) method, which interrogates individual chromatin marks in the context of combinatorial chromatin states. Based on results from these approaches, we propose the hypothesis that cytosine methylation (5mC) and histone methylation H3K36me may synergistically repress production of natural antisense transcripts (NATs) in the context of actively expressed genes. Mutant analyses supported this proposed model at a significant proportion of the tested loci. We further identified polymerase‐associated factor as a potential repressor for NAT abundance. Although the majority of tested NATs were found to localize to the nucleus, we also found evidence for cytoplasmically partitioned NATs. The significance of the subcellular localization of NATs and their biological functions remain to be defined.